EFISIENSI INVESTASI DAN OPTIMALISASI ASET TETAP PADA INSTITUSI PENDIDIKAN - Anggraeni, Fanny; Sasongko, Catur (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2019)
This research discussed about the investment efficiency and optimization of fixed asset in X University. This research aims to answer the research questions regarding the efficiency of fixed asset investment conducted by X University and how to optimize fixed asset investment carried out by X University. Performance theory is used in this research. This research is a case study with a sequential mixed-method approach. Researchers use primary data in the form of interviews with related parts, and secondary data in the form of data regarding costs related to fixed asset investment. Data analysis is done by analyzing content. The results indicate that fixed asset investment carried out by University X is not yet efficient. The results of the interview also support these findings. This research is expected to help X University to optimize their fixed assets so that their investments become efficient.